Karakteristik dan Kapaistas Vital Paksa Paru Pekerja Bagian Produksi Aspal Hotmix PT. Sabaritha Perkasa Abadi Tahun 2014 - Dyah Ayu Wulandari; lina tarigan; halinda saari lubis (Lingkungan dan Kesehatan Kerja, 2014)
Hazards at the workplace like dust exposure could interference the respiratory functionimpairment effects. Several factors of the worker’s characteristics itself could affect the lungcondition such as age, smoking habits, medical history, personal protective equipment, nutritionalstatus, exercise habits and working period. The purpose of this research is to know the descriptionof the characteristics and lung forced of vital capacity of workers at hot mix asphalt production inPT. Sabaritha Perkasa Abadi 2014.This research is a descriptive research with cross-sectional design, with sample is 12 people(Total Sampling). To analize of data is using descriptive statistics where each variable of theresearch will be presented in the form of frequency distribution table The results of researchshowed that 6 workers (50.0 %) aged less than 32 years old and 6 (50.0 %) of workers aged over32 years, all workers have no history of pulmonary disease, 11 workers (91.7 %) are smoker and 10workers (90.9 %) are light smokers, 9 workers (75.0 %) wearing PPE (Personal ProtectionEquipment) in workplace , 7 workers (58,3 %) worked under 1 years, 8 workers (66.7 %) havenormal nutritional status, 11 workers (91.7 %) not exercising, and the results of forced vitalcapacity test showed that all workers had normal forced vital capacity.The suggestion are the company have to make a smoking ban in workplace, provide PPE forworkers and make all workers to wear it, do the workers examination in regularly, workers have tostop smoke and doing of exercise regularly.Keywords : Characteristics, Lung Forced Vital Capacity, Hotmix Asphalt.